2022
DOI: 10.1145/3505590
|View full text |Cite
|
Sign up to set email alerts
|

Physecology: A Conceptual Framework to Describe Data Physicalizations in their Real-World Context

Abstract: The standard definition for “physicalizations” is “a physical artifact whose geometry or material properties encode data”  [ 47 ]. While this working definition provides the fundamental groundwork for conceptualizing physicalization, in practice many physicalization systems go beyond the scope of this definition as they consist of distributed physical and digital elements that involve complex interaction mechanisms. In this article, we examine how “physicalizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 83 publications
1
9
0
Order By: Relevance
“…The study on Physikit [19] showed that when households spent most time at home, they were able to make sense of the data as they were regularly exposed to the PhysiCubes. Hence, this implicates that an environmental coupling [38] -in which the physicalization is co-located with its audience -could support regular engagement and sense-making of the data. Moreover, an environmental coupling [38] between the data sculpture and its users allows for people to be flexible when submitting data.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The study on Physikit [19] showed that when households spent most time at home, they were able to make sense of the data as they were regularly exposed to the PhysiCubes. Hence, this implicates that an environmental coupling [38] -in which the physicalization is co-located with its audience -could support regular engagement and sense-making of the data. Moreover, an environmental coupling [38] between the data sculpture and its users allows for people to be flexible when submitting data.…”
Section: Discussionmentioning
confidence: 87%
“…Hence, this implicates that an environmental coupling [38] -in which the physicalization is co-located with its audience -could support regular engagement and sense-making of the data. Moreover, an environmental coupling [38] between the data sculpture and its users allows for people to be flexible when submitting data. Future research could further investigate the influence of different spatial couplings on environmental awareness.…”
Section: Discussionmentioning
confidence: 87%
“…Designers and researchers have been exploring the growing space of data physicalizations [6,25], including the elements that constitute its ecology [71]. They integrate principles from Data Visualization, Interaction Design, and Human-computer Interaction to create a myriad of artifacts that represent data through their physical properties.…”
Section: Data Physicalization Practices and Sustainabilitymentioning
confidence: 99%
“…If these issues are not addressed, information communication in data physicalization can fail. At first, an easy way to overcome these issues could be to use digital color palettes [7][8][9][10], or define them manually, to be applied directly to data physicalization, leading to the low efficiency of the color to communicate data [6].…”
Section: Introductionmentioning
confidence: 99%